(untitled) (Journal of Plant Disease Sciences, 2025)
Banana production is increasingly threatened by viral pathogens, particularly Banana bunchy top virus (BBTV) and (CMV). These viruses reduce crop yield and quality, making the early and accurate detection of infections critical for effective disease control. BBTV symptoms can take between 25 to 85 days to appear following transmission by aphids ( ), which complicates timely diagnosis. In this study, a PCR-based assay was developed to simultaneously detect BBTV and CMV by targeting conserved regions of their respective movement protein (MP), replication-associated (Rep), and coat protein (CP) genes. Banana leaf samples were collected from major cultivation areas across different agroclimatic zones in Maharashtra. An internal control was included to ensure the reliability of PCR amplification. The method proved effective for rapid and specific virus identification, offering an improvement over single-gene PCR by minimizing false positives. This diagnostic approach can support routine screening programs to ensure the propagation of virus-free planting material, thereby enhancing disease management and improving yields in Banana